A panel unit root and panel cointegration test of the complementarity hypothesis in the Mexican case, 1960-2001 - Miguel D. Ramirez (Yale University, Economic Growth Center, 2007)
Using panel data, this paper tests whether public and private capital have a positive and significant effect on aggregate output and labor productivity for Mexico during the 1960-2001 period. The richer information set made possible by the sectorial data enables this study to utilize the methodologically sound "group-mean" Fully Modified Ordinary Least Squares (FMOLS) procedure developed by Pedroni to generate consistent estimates of the relevant panel variables in the cointegrated production (labor productivity) function. The resu lts suggest that, in the long run, changes in the stocks of public and private capital and the economically active population (EAP) have a positive and economically significant effect on output ( and labor productivity). The period is also broken down into two sub-periods: 1960-81 (state-led industrialization) and 1982-2001 (neoliberal model). The estimate for the public capital variables clearly shows that it had a relatively more important economic effect during the earlier state-led period.
Keywords: O10; O50; O40; 330; Fully modified ordinary least squares (FMOLS); panel unit roots; panel cointegration test; complementarity hypothesis; Mexican labor productivity